DISCOURSE MARKERS IN ESSAY WRITING OF SENIOR HIGH SCHOOL STUDENTS - Sonya Sibagariang; Siti Aisah Ginting; Berlin Sibarani (Universitas Negeri Medan, 2018)
The objectives of the study were to find out the discourse markers naturally that used by students in the essay writing, the most frequent inappropriateness in terms of the use of discourse markers, and to describe the reasons why they used the discourse markers in the way they do. The study was conducted by applying a descriptive qualitative research. The subjects of the research were the students of senior high school at SMA Budisatrya Medan. The data were the students’ writing that were analyzed by using Fraser Taxonomy (1999). It was fond that the students used 7 out 8 types of discourse markers. Furthermore, the data were also analyzed by using Kao & Chen Taxonomy (2011). It was also fond that the students used 3 out 6 types of misuse patterns of discourse markers. There were seven reasons the students used discourse markers: Limitation of knowledge, lack of ability in writing, lack of interest against english, lack of interest against writing, reading resources, teachers’ explanation and internet resources. Keywords: Discourse Markers, Misuse Patterns, Students’ essay writing.